Factors affecting students’ intention to use artificial intelligence in learning: An empirical study in Vietnam - Hoai, Nguyen Thu (Edelweiss Applied Science and Technology, 2025)
This study was conducted to evaluate the factors affecting students’ intention to use artificial intelligence (AI) in their learning process in the context of Vietnam. A mixed-method approach, which combined both quantitative and qualitative analysis, was used in this study. The research model was built based on the technology acceptance model (TAM). The research results with 404 students at universities in Vietnam showed that the intention to use AI was influenced by the factors of perceived ease of use and perceived usefulness of AI. The study also provided some implications for universities, developers, and service providers related to AI to increase the value of AI in students’ learning process.